The Contribution and Philosophical Development of the Reformational Philosopher Herman Dooyeweerd: An Historical Overview - Ive, Jeremy (Koers (Potchefstroom, South Africa), 2024)
Herman Dooyeweerd and Dirk H. Th. Vollenhoven played complementary roles in the development of Reformational philosophy. This paper examines the role that Dooyeweerd had to play and examines the development of his philosophy.